Consolidated Edison's building
The entire facade of Consolidated Edison's building at the New York World's Fair is a 9,000 square foot sheet of water sent up 42 feet into the air by individual fountains - made even more beautiful by lighting and color. Inside is the spectacular diorama - The City of Light.